2012
DOI: 10.1007/s11434-012-5001-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of leaf rust resistance gene Lr34 and lesion mimic gene lm significantly enhances adult plant resistance to Puccinia triticina in wheat

Abstract: Leaf rust caused by Puccinia triticina is an economically-important disease in wheat worldwide. A combination of different types of resistance genes may significantly enhance rust resistance under rust-favorable conditions. To investigate the interactions between the rust resistance gene Lr34 and the lesion mimic gene lm on 1BL in Ning 7840, a segregating F 8-10 population of 180 recombinant inbred lines was developed from Ning 7840/Chokwang and evaluated for both lesion mimic expression and leaf rust response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…On chromosome 7BS, markers GBS_1203 (68.9 cM), GBS_18119 (68.9 cM), and GBS_23290 (68.9 cM) were significant in the Njoro main and off‐seasons, while GBS_15572 (68.9 cM) was significant only in the Njoro main season. There has been only one previous study (Li et al, 2012) that detected a marker, Xgwm361.2 on chromosome 7BS, that was positively correlated to the length of LTN in a population developed from Ning 7840/Chokwang. However, the position of this marker was not available in the Synthetic × Opata map, for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…On chromosome 7BS, markers GBS_1203 (68.9 cM), GBS_18119 (68.9 cM), and GBS_23290 (68.9 cM) were significant in the Njoro main and off‐seasons, while GBS_15572 (68.9 cM) was significant only in the Njoro main season. There has been only one previous study (Li et al, 2012) that detected a marker, Xgwm361.2 on chromosome 7BS, that was positively correlated to the length of LTN in a population developed from Ning 7840/Chokwang. However, the position of this marker was not available in the Synthetic × Opata map, for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that N regulates the LM phenotype in wheat variety P7001, and the LM disappeared under high dosages of N supply (Li et al, 2016a). In our previous study, we found that wheat variety Ning7840 has LM phenotype (Li & Bai, 2009; Li, Bai & Gu, 2012), and the current study showed that the LM phenotype in Ning7840 is also regulated by N. LM in other plants such as Arabidopsis, rice, maize and barley have also been reported, but the relationship between N supply and LM traits remains to be determined. P7001 and Ning7840 are unrelated to each other according to their pedigrees, suggesting N may play an important role in the regulation of LM expression in wheat.…”
Section: Discussionmentioning
confidence: 48%
“…We first reported a trait N dosage dependent hypersensitive reaction-like (HRL, also referred to as LM) in wheat variety P7001 (Li et al, 2016a). Our previous studies showed that wheat variety Ning7840 has LM phenotype at heading stage (Li & Bai, 2009; Li, Bai & Gu, 2012), while two EMS-induced mutants of Ning7840, Dlm1 and Dlm2 , showed the absence of LM (Li et al, 2016b). Interestingly, we found that Ning7840 and its two mutants mentioned above have markedly different responses to N application, where LM in Ning7840 was sensitive to N dosage whereas the absence of LM in the two mutants were insensitive to N dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizarea rezistenţei genetice parţiale, nespecifice, de plantă adultă reprezintă o premiză pentru mărirea durabilităţii rezistenţei grâului, independent de evoluţia climei şi a virulenţei agentului patogen [8,9]. S-au observat efecte aditive pentru diferite gene care conferă rezistenţă la rugină brună, şi totodată, efecte epistatice -pentru tipul de infecţie [10].…”
Section: Introducereunclassified